The Effects of Self Reminder Card to the Successful Treatment of Blood Pressure of Hypertension Patients in Community Health Centers in Surabaya - Selly Septi Fandinata; Iin Ernawati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Hypertension treatment aims to control blood pressure. Self-reminder card is a tool that can help patients to avoid forget in taking the medicine. The purpose of determine the effects of self-reminder cards on the successful treatment of blood pressure in hypertension patients at community health centers in Surabaya. Research design Quasi Experimental control and self-reminder card group pre post prospective with Wilcoxon and Mann Whitney test Analysis. The sample was 115 patients. The results showed that the systolic blood pressure of the patients pre post the intervention group (p = 0.009) and test of both groups (p = 0.009) so that effect the successful in reducing systolic blood pressure of hypertension patients. In the pre post diastolic blood pressure of the intervention group (p = 0.016) and test was conducted for both groups (p = 0.935) so that no effect the successful in reducing diastolic blood pressure in hypertension patients.